Exploring the Moderating Effect of Entrepreneurial Activity on the Finance-Growth Nexus in Africa? - ADUSEI, Michael (Asian Journal of Empirical Research, 2013)
The paper uses data from 12 African countries to examine whether entrepreneurial activity moderates the relationship between financial development and economic growth. Using panel Generalized Method of Moments (GMM) technique, the results show that entrepreneurial activity does not moderate the relationship between finance and economic growth. The study also finds that economic openness of the study countries is inimical to their growth. To the extent that the interaction between finance and entrepreneurial activity does not significantly influence economic growth, we strongly recommend that African countries should review their financial systems and entrepreneurship-development programs.